MEDIA "AMMAR PUZZLE" SEBAGAI INOVASI GAMIFIKASI: STRATEGI REVOLUSIONER DALAM PEMBELAJARAN SHALAT AKHLAK (PAI) DI SD ICP AL-FALAH DARUSSALAM - Azis, Annisa Rahmania; Soraya, Irma; Kurjum, Mohammad (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study examines the effectiveness of Ammar Puzzle as a gamification-based innovation in Shalat Akhlak learning at SD ICP Al-Falah Darussalam Tropodo. This study employs a a field research with a descriptive qualitative approach.. Data collection techniques include observation, interviews, and documentation. The findings reveal that: 1) “Ammar Puzzle” is designed to enhance students' motivation and engagement through visual, auditory, and kinesthetic approaches; 2) The implementation of this media effectively improves students' focus and understanding of Shalat Akhlak through interactive and collaborative learning methods; 3) The challenges in using Ammar Puzzle include limited instructional time and varying levels of student comprehension, while the supporting factors consist of teacher support and students’ enthusiasm for game-based learning. Additionally, the application of this media contributes to improving students' social skills and teamwork in understanding Islamic values. Thus, Ammar Puzzle serves as an innovative alternative that can be applied in Islamic Religious Education (PAI) to create a more engaging, interactive, and meaningful learning experience.